2020
DOI: 10.1177/0022034520945242
|View full text |Cite
|
Sign up to set email alerts
|

Association or Causation? Exploring the Oral Microbiome and Cancer Links

Abstract: Several epidemiological investigations have found associations between poor oral health and different types of cancer, including colorectal, lung, pancreatic, and oral malignancies. The oral health parameters underlying these relationships include deficient oral hygiene, gingival bleeding, and bone and tooth loss. These parameters are related to periodontal diseases, which are directly and indirectly mediated by oral bacteria. Given the increased accessibility of microbial sequencing platforms, many recent stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 59 publications
0
47
0
2
Order By: Relevance
“…Several hypotheses have been put forward to explain the connecting link between periodontitis and cancer, but the basic biological mechanisms still remains unclear (Meurman, 2010). The following describes the mechanisms of carcinogenesis that are regulated commensal microorganisms (Eslami et al, 2020;Bakhti and Latifi-Navid, 2021;Meurman, 2010;Teles et al, 2020).…”
Section: Mechanisms Involved In Periodontitis-linked Carcinogenesismentioning
confidence: 99%
“…Several hypotheses have been put forward to explain the connecting link between periodontitis and cancer, but the basic biological mechanisms still remains unclear (Meurman, 2010). The following describes the mechanisms of carcinogenesis that are regulated commensal microorganisms (Eslami et al, 2020;Bakhti and Latifi-Navid, 2021;Meurman, 2010;Teles et al, 2020).…”
Section: Mechanisms Involved In Periodontitis-linked Carcinogenesismentioning
confidence: 99%
“…Several studies showed that there is a relationship between the human oral microbiome and certain systemic diseases, such as pancreatic cancer [8], Type 2 diabetes [9], pediatric Crohn's disease [10], heart disease [11], and low-weight preterm birth [12]. Certain oral bacterial species may contribute to carcinogenesis [13]. The role of the oral microbiome involves the mediation of inflammation related to changes in systemic health and disease [14].…”
Section: Introductionmentioning
confidence: 99%
“…The time is not now but we need to start planning for that future by thinking about what can be done now to prepare. In addition, research is examining the relationship of the oral microbiome and various cancers including oral cancer [ 86 ]. If new risk factors are identified that more precisely predict oral or oropharyngeal cancer risk, the CDS could incorporate new evidence brought to the dental provider at the point of care.…”
Section: Discussionmentioning
confidence: 99%